The significance of tax revenues on the volume of the government budget deficit - Janković Gordan (Trendovi u Poslovanju)
The budget is a set of all planned revenues and expenditures of individuals and corporations, institutions, the state... for a certain time frame, usually per year. We will put emphasis on the government budget. In a situation where exactly these planned revenues are at a lower level compared to planned expenditures, a government budget deficit occurs. The big problem of the modern states is the chronic budget deficit. It arises in a situation where a negative gap between public revenues and expenditures appears every year for a long period of time. The so-called tax revenues have a huge importance in the public revenues of the budgets of modern states. In the paper itself, we will pay attention to tax revenues. We will show an empirical presentation of the trends in the structure of these revenues in countries with different levels of income per capita, we will analyze the impact of tax revenues on the level of the budget deficit. The structure of tax revenues largely depends on the level of development of that country's economy.